Cystatin C versus Creatinine as Early Stage Diabetic Nephropathy Marker - Atteaya Zaman , Amena Rahim , Muhammad Afzal , Abdul Khaliq Naveed (Journal of Islamic International Medical College, 2018)
Objective: To compare the levels of serum cystatin and creatinine as the markers of early stage of diabetic nephropathy. Study Design: Case Control study. Place and Duration of Study: The study was conducted at Railway Hospital, Rawalpindi for a period of one year from March 15 , 2016 to March 16 , 2017. Materials and Methods: A total of 77 diabetics and 77 healthy controls were selected. These included adults above 40 years of age. The levels of Serum cystatin C and creatinine were measured using IMAGIN Specific Protein Analyzer. Both tests were done by applying standardized laboratory protocols. The study outcome was determined in terms of detection of diabetic nephropathy which was finalized on the basis of albuminuria status derived as three categories; normoalbuminuric, microalbuminuria and macroalbuminuria. Results: Male cases were more than females (58.4% vs 41.6%), and were equally distributed in patients and control groups. The levels of Cystatin C (4.7 + 3.9 mg/l), and creatinine (1.0 + 0.13 mg/dl) were found significantly high in the macroalbuminuria group as compared to controls and normoalbuminuric group (pvalue <0.001). Serum cystatin C was significantly raised in microalbuminurics as compared to serum creatinine proving its worth for detecting early stage diabetic nephropathy (p-value <0.001). Conclusion: Serum cystatin C is a better predictive marker of diabetic nephropathy than serum creatinine.